Multistakeholder Internet Governance? - Dutton, William H. (World Bank, Washington, DC, 2016)
Global debate over alternative approaches to governing the Internet has been wide ranging, but increasingly has pivoted around the wisdom of “multistakeholder governance.” This paper takes controversy around a multistakeholder versus an alternative multilateral approach as a focus for clarifying the changing context and significance of Internet governance. A critical perspective on this debate challenges some of the conventional wisdom marshaled around positions on the history and future of Internet governance. By providing an understanding of the dynamics of Internet governance, this paper seeks to illuminate and engage with issues that are of rising importance to the vitality of a global infrastructure that is becoming more central to economic and social development around the world. Based on the perspective developed in this paper, a multistakeholder process appears best suited for helping a widening array of actors, including multilateral organizations, to connect a worldwide ecology of choices that are governing the Internet.